Different Factors Are Associated With Sex Hormones and Leydig Cell Function in Israelis and Palestinians in Jerusalem. Issue 4 (July 2022) - Vishnevsky, Guy; Sinnreich, Ronit; Nassar, Hisham; Merom, Dafna; Ish-Shalom, Maya; Kark, Jeremy D.; Levine, Hagai
Total testosterone (TT) is known to influence health and virility in men. Among men from United States and Europe, numerous sociodemographic and lifestyle factors were reported to be associated with TT. However, associations with TT and Leydig cell function in the Middle East are poorly described. A cross-sectional, population-based sample had a structured interview, physical examinations, and blood tests in two hospitals in Jerusalem, Israel. A subsample (25- to 44-year-old men, n = 286: 124 Israelis, 162 Palestinians) had sex hormone measurements. The primary outcomes were TT and free testosterone/luteinizing hormone (FT/LH) ratio, representing Leydig cell function. Associations with sociodemographic and lifestyle factors, body mass index (BMI), and physical activity (PA) were evaluated using multivariable linear regression. Compared with Palestinians, Israelis had similar TT (4.81 vs. 5.09 ng/mL, p = .405) and higher FT/LH (31.2 vs. 25.8 ng/IU, p = .002). In ln-transformed values, marital status had a stronger association in Palestinians (P for interaction = 0.03). Age, BMI, and PA had a stronger association with TT in Israelis with significant interactions with ethnicity. BMI <25 and a higher PA quartile were associated with a higher TT ( p < .001). Among Israelis, age ( p = .007), married marital status ( p = .007), and BMI <25 were significantly associated with FT/LH. No associations of any factors were identified among Palestinians. Associations with several modifiable factors identified in Western samples were replicated in Israelis and to a lesser degree in Palestinians. Different relationships of several factors with TT and FT/LH could result from ethnically diverse genetic, sociodemographic, and behavioral characteristics that warrant further research.